Ultrasonic inspection technology development and search unit design : examples of practical applications - Brook, Mark V. (Hoboken, N.J. : IEEE Press, 2011)
'Ultrasonic testing is a relatively new branch of science and industry. The development of ultrasonic testing started in the late 1920s. At the beginning, the fundamentals of this method were borrowed from basic physics, geometrical and wave optics, acoustics and seismology. Later it became clear that some of these theories and calculation methods could not always explain the phenomena observed in many specific cases of ultrasonic testing. Without knowing the nuances of the ultrasonic wave propagation in the test object it is impossible to design effective inspection technique and search units for it realization. This book clarifies the theoretical differences of ultrasonics from the other wave propagation theories presenting both basics of physics in the wave propagation, elementary mathematic and advanced practical applications. Almost every specific technique presented in this book is proofed by actual experimental data and examples of calculations'--
'This book clarifies the theoretical differences of ultrasonics from the other wave propagation theories presenting both basics of physics in the wave propagation, elementary mathematic and advanced practical applications'--
Includes bibliographical references and index.
Keywords: Ultrasonic testing; Ultrasonic waves -- Industrial applications